The Influence of Teachers' Pedagogic Competence on Student Learning Activity - Nasaruddin Hasyim; Arfiani Arfiani; Sirajuddin Saleh (ASHA Publishing, 2024)
Student activity during the teaching and learning process is one of the indicators of students' desire or motivation to learn. One of the factors that affects learning activity is the pedagogic competence factor of teachers. This study aims to find out the picture of teachers' pedagogic competence and the picture of student learning activity as well as to analyze the influence of teachers' pedagogic competence on the learning activity of grade XI students of SMA Negeri 7 Sinjai. This study uses a quantitative method with an associative research type. The population in this study is 154 grade XI students with a sample of 77 students. Data collection was carried out by observation, questionnaire, and documentation techniques. The data analysis techniques in this study use descriptive statistical analysis and inferential statistical analysis. The results of the study show that the pedagogic competence of teachers is classified as good. Students' learning activity is classified as good. The results of hypothesis testing show that there is a positive and significant influence of teachers' pedagogic competence on the learning activity of grade XI students of SMA Negeri 7 Sinjai